Were They Tortured or Did They Make that Up? Ethnographic Reflections on Torture Allegations in the Basque Country in Spain - Carolijn Terwindt (Oñati Socio-Legal Series)
Academic literature about torture has addressed a wide range of questions. An important facet, however, has not yet received sufficient attention. Given that torture tends to occur in secrecy, how does the lack of information that is perceived to be objective and authoritative affect the societal response to allegations of torture and the social consequences of such allegations?  In this article, the controversy about torture allegations in Spain is used to examine this issue and explore the insidious effects the uncertainty has on society.  The Spanish state is unable to provide a generally accepted account in response to the continuous torture allegations from Basque prisoners accused of terrorism or street violence.   Based on ethnographic research, this article describes how Spanish and Basque society can be divided in believers, non-believers and people who do not care about torture allegations.  Because of the centrality of such allegations in many criminal cases, this division also polarizes public perceptions of the entire criminal justice system.